Nano‐Localized Heating Source for Photonics and Plasmonics. Issue 12 (25th August 2013) - De Sio, Luciano; Placido, Tiziana; Serak, Svetlana; Comparelli, Roberto; Tamborra, Michela; Tabiryan, Nelson; Curri, M. Lucia; Bartolino, Roberto; Umeton, Cesare; Bunning, Timothy
<x xml:space="preserve">Abstract</x> Gold nanorods embedded in a cholesteric liquid crystal (CLC) enable control of both the "selective reflection" of the CLC and the "plasmonic resonance" of near infrared radiation, thus allowing realization of a bridging between photonics and plasmonics in these materials. These results open up the detection of nanoscale temperature variations, with possible future application in nanomedicine. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>